Integrative Taxonomy of Australian Metopia (Sarcophagidae: Miltogramminae) Reveals a New Species and Challenges Traditional Phylogeny. Issue 6 (4th December 2020) - Johnston, Nikolas P; Wallman, James F; Pape, Thomas
Abstract: A taxonomic revision of all Australian species of Metopia Meigen (Sarcophagidae: Miltogramminae) is completed using an integrated approach combining molecular and morphological data. Metopia nudibasis (Malloch) is redescribed as a species complex and a new endemic Australian species, Metopia sputnik sp. n., is described. Evidence is presented that Metopia sauteri (Townsend) is absent from Australia and this species is therefore removed from the known Australian fauna. Molecular phylogenetics is used to reconstruct interspecific and generic relationships and support morphology-based species hypotheses. Phylogenetic analysis splits Metopia Meigen into two clades, separated by Aenigmetopia Malloch, rendering the former genus nonmonophyletic. The implications of this are discussed.